Codesigning health and other public services with vulnerable and disadvantaged populations: Insights from an international collaboration. (2nd January 2019) - Mulvale, Gillian; Moll, Sandra; Miatello, Ashleigh; Robert, Glenn; Larkin, Michael; Palmer, Victoria J.; Powell, Alicia; Gable, Chelsea; Girling, Melissa
Abstract: Background: Codesign has the potential to transform health and other public services. To avoid unintentionally reinforcing existing inequities, better understanding is needed of how to facilitate involvement of vulnerable populations in acceptable, ethical and effective codesign. Objective: To explore citizens' involvement in codesigning public services for vulnerable groups, identify challenges and suggest improvements. Design: A modified case study approach. Pattern matching was used to compare reported challenges with a priori theoretical propositions. Setting and participants: A two‐day international symposium involved 28 practitioners, academics and service users from seven countries to reflect on challenges and to codesign improved processes for involving vulnerable populations. Intervention studied: Eight case studies working with vulnerable and disadvantaged populations in three countries. Results: We identified five shared challenges to meaningful, sustained participation of vulnerable populations: engagement; power differentials; health concerns; funding; and other economic/social circumstances. In response, a focus on relationships and flexibility is essential. We encourage codesign projects to enact a set of principles or heuristics rather than following pre‐specified steps. We identify a set of principles and tactics, relating to challenges outlined in our case studies, which may help in codesigning public services with vulnerable populations. Discussion and conclusions: Codesign facilitators must consider how meaningful engagement will be achieved and how power differentials will be managed when working with services for vulnerable populations. The need for flexibility and responsiveness to service user needs may challenge expectations about timelines and outcomes. User‐centred evaluations of codesigned public services are needed.